Effect of enhanced psychosocial care on antipsychotic use in nursing home residents with severe dementia: cluster randomised trial. Issue 7544 (16th March 2006) - Fossey, Jane; Ballard, Clive; Juszczak, Edmund; James, Ian; Alder, Nicola; Jacoby, Robin; Howard, Robert
Abstract: Objective To evaluate the effectiveness of a training and support intervention for nursing home staff in reducing the proportion of residents with dementia who are prescribed neuroleptics. Design Cluster randomised controlled trial with blinded assessment of outcome. Setting 12 specialist nursing homes for people with dementia in London, Newcastle, and Oxford. Participants Residents of the 12 nursing homes; numbers varied during the study period. Intervention Training and support intervention delivered to nursing home staff over 10 months, focusing on alternatives to drugs for the management of agitated behaviour in dementia. Main outcome measures Proportion of residents in each home who were prescribed neuroleptics and mean levels of agitated and disruptive behaviour (Cohen-Mansfield agitation inventory) in each home at 12 months. Results At 12 months the proportion of residents taking neuroleptics in the intervention homes (23.0%) was significantly lower than that in the control homes (42.1%): average reduction in neuroleptic use 19.1% (95% confidence interval 0.5% to 37.7%). No significant differences were found in the levels of agitated or disruptive behaviour between intervention and control homes. Conclusions Promotion of person centred care and good practice in the management of patients with dementia with behavioural symptoms provides an effective alternative to neuroleptics.